2022
DOI: 10.1371/journal.pone.0279371
|View full text |Cite
|
Sign up to set email alerts
|

Modeling post-holiday surge in COVID-19 cases in Pennsylvania counties

Abstract: COVID-19 arrived in the United States in early 2020, with cases quickly being reported in many states including Pennsylvania. Many statistical models have been proposed to understand the trends of the COVID-19 pandemic and factors associated with increasing cases. While Poisson regression is a natural choice to model case counts, this approach fails to account for correlation due to spatial locations. Being a contagious disease and often spreading through community infections, the number of COVID-19 cases are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…Regarding the increase in the number of cases and deaths in months with specific holidays, a study carried out by Ren and Hwang [20] corroborates this research, which shows that approximately six to eight days after a holiday, there was an increase of 1.30 to 1.41 times the incidence rate. This expected time is directly related to the period of manifestation of symptoms and/or the results of the exam performed.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Regarding the increase in the number of cases and deaths in months with specific holidays, a study carried out by Ren and Hwang [20] corroborates this research, which shows that approximately six to eight days after a holiday, there was an increase of 1.30 to 1.41 times the incidence rate. This expected time is directly related to the period of manifestation of symptoms and/or the results of the exam performed.…”
Section: Discussionsupporting
confidence: 61%
“…A study conducted in the United States revealed that the period significantly impacting the number of confirmed cases corresponds to holidays such as New Year’s Day, Martin Luther King Day, Good Friday, Independence Day, Memorial Day, Labor Day, Christmas, elections, vacations, among others [ 20 ]. In this regard, it aligns with the data found in our research, considering that these months also have similar holidays in Brazil, such as Christmas, New Year’s, elections, and vacation periods, leading to an increase in the number of people circulating, as well as group gatherings.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the increase in the number of cases and deaths in months with specific holidays, a study carried out by Ren and Hwang [20] corroborates this research, which shows that in approximately six to eight days after a holiday, there was an increase of 1.30 to 1.41 times the incidence rate. This expected time is directly related to the period of manifestation of symptoms and/or the results of the exam performed.…”
Section: Discussionsupporting
confidence: 60%
“…For the analyzes of a study carried out in the United States, federal holidays were considered, such as New Year, Martin Luther King Day, Good Friday, Independence Day, Memorial Day, Labor Day, Christmas, elections, vacations, among others [20]. This finding is in line with the results of the current study, considering that these are months that have similar holidays in Brazil, such as Christmas, New Year, elections, in addition to the vacation period, which leads to an increase in the number of people circulating, as well as, group meetings.…”
Section: Discussionmentioning
confidence: 99%